2007
DOI: 10.1007/s00134-007-0568-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergency feasibility in medical intensive care unit of extracorporeal life support for refractory cardiac arrest

Abstract: Emergency ECLS is feasible in medical ICU and should be considered as a resuscitative tool for selected patients suffering from refractory cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(98 citation statements)
references
References 36 publications
3
86
2
7
Order By: Relevance
“…Extracorporeal membrane oxygenation (ECMO) should be considered for rescuing patients with refractory cardiogenic shock [1][2][3][4][5][6][7][8][9][10]. It has been successfully used as a bridge to myocardial recovery, cardiac transplantation, or implantation of a ventricular assist device (VAD) in patients with overt cardiac failure's various etiologies, e.g., acute myocardial infarction [7,11], end-stage dilated cardiomyopathy [9], viral or toxic myocarditis [12][13][14], complications of cardiac surgery [8,15,16], or cardiac arrest [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO) should be considered for rescuing patients with refractory cardiogenic shock [1][2][3][4][5][6][7][8][9][10]. It has been successfully used as a bridge to myocardial recovery, cardiac transplantation, or implantation of a ventricular assist device (VAD) in patients with overt cardiac failure's various etiologies, e.g., acute myocardial infarction [7,11], end-stage dilated cardiomyopathy [9], viral or toxic myocarditis [12][13][14], complications of cardiac surgery [8,15,16], or cardiac arrest [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…10 In 1995, Davies et al reported the first use of ECMO as a support for massive pulmonary embolism. 11 ECMO helps in acute right ventricular failure by diverting blood from the right atrium to arterial circulation, unloading the right ventricle and relieving its dilation.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of extracorporeal CPR for in-hospital cardiac arrest has been reported [4][5][6][7]. Especially, refractory ventricular arrhythmia has been demonstrated to be a good indicator for starting this alternative CPR method [6,7].…”
Section: Discussionmentioning
confidence: 99%